Study on Active and Passive Control of Order Vibration for Electric Vehicle Power Train - Yuanyuan Zhang; Peng Yu; Jian Wang (Jixie chuandong)
Abstract A whole order vibration reduction method for electric powertrain is proposed. Firstly， motor control strategy is optimized and the output torque ripple is reduced by inhibiting main harmonic currents of motor d-q axial，based on harmonic optimization theory. Secondly，in consideration of active control effect，the best gear modification parameters are obtained，transmission error volatility is reduced by joint optimization with elitist retention genetic algorithm and gear engagement finite element model. Finally， order vibration control effect after tooth modification is verified by establishing electric vehicle power train mechanical simulation model. The results show that， comprehensive consideration of the motor harmonic current control and the microscopic modification of gear tooth， can effectively reduce the order vibration of electric vehicle power train.